Cryotherapy versus salicylic acid for the treatment of plantar warts (verrucae): a randomised controlled trial. (7th June 2011) - Cockayne, Sarah; Hewitt, Catherine; Hicks, Kate; Jayakody, Shalmini; Kang'ombe, Arthur Ricky; Stamuli, Eugena; Turner, Gwen; Thomas, Kim; Curran, Mike; Denby, Gary; Hashmi, Farina; McIntosh, Caroline; et al.
Abstract : Objective To compare the clinical effectiveness of cryotherapy versus salicylic acid for the treatment of plantar warts. Design A multicentre, open, two arm randomised controlled trial. Setting University podiatry school clinics, NHS podiatry clinics, and primary care in England, Scotland, and Ireland. Participants 240 patients aged 12 years and over, with a plantar wart that in the opinion of the healthcare professional was suitable for treatment with both cryotherapy and salicylic acid. Interventions Cryotherapy with liquid nitrogen delivered by a healthcare professional, up to four treatments two to three weeks apart. Patient self treatment with 50% salicylic acid (Verrugon) daily up to a maximum of eight weeks. Main outcome measures Complete clearance of all plantar warts at 12 weeks. Secondary outcomes were ( a ) complete clearance of all plantar warts at 12 weeks controlling for age, whether the wart had been treated previously, and type of wart, ( b ) patient self reported clearance of plantar warts at six months, ( c ) time to clearance of plantar wart, ( d ) number of plantar warts at 12 weeks, and ( e ) patient satisfaction with the treatment. Results There was no evidence of a difference between the salicylic acid and cryotherapy groups in the proportions of participants with complete clearance of all plantar warts at 12 weeks (17/119 (14%) v 15/110 (14%), difference 0.65% (95% CI –8.33 to 9.63), P=0.89). The results did not change when the analysis was repeated but with adjustment for age, whether the wart had been treated previously, and type of plantar wart or for patients' preferences at baseline. There was no evidence of a difference between the salicylic acid and cryotherapy groups in self reported clearance of plantar warts at six months (29/95 (31%) v 33/98 (34%), difference –3.15% (–16.31 to 10.02), P=0.64) or in time to clearance (hazard ratio 0.80 (95% CI 0.51 to 1.25), P=0.33). There was also no evidence of a difference in the number of plantar warts at 12 weeks (incident rate ratio 1.08 (0.81 to 1.43), P=0.62). Conclusions Salicylic acid and the cryotherapy were equally effective for clearance of plantar warts. Trial registration Current Controlled Trials ISRCTN18994246, National Research Register N0484189151.